IMPLEMENTASI KURIKULUM MERDEKA DALAM MERANCANG DAN MELAKSANAKAN MODUL AJAR PADA MAHASISWA PRODI PENDIDIKAN BAHASA DAN SASTRA INDONESIA - Titin Nurhayatin; Regina, Frilia Shantika (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
The curriculum changes along with the demands of the times and learning needs. Today's learning demands are very complex. Educators must be able to design learning creatively and innovatively. In 21st century learning, educators are required to be able to develop critical thinking skills, collaboration skills, creativity skills and communication skills. These four abilities must be formed through classroom learning. Education must be able to produce students who have strong national character, are independent and have high competitiveness. Therefore, in the curriculum of the Indonesian Language and Literature Education Study Program FKIP Pasundan University, the Curriculum Study, Planning and Implementation of Learning courses are the main courses aimed at preparing students' competence in planning and implementing learning. This research uses a quantitative descriptive method with data collection techniques based on the value of preparing learning tools based on the Independent Curriculum, the value of observing the learning practice process carried out using peer teaching techniques involving other lecturers as observers. The data collection technique used the entire student population who contracted the Curriculum Study, Planning and Learning Implementation course, 65 people. Based on the results of the research conducted, it can be concluded that students in the Indonesian Language and Literature Education Study Program FKIP Pasundan University are able to design learning in accordance with the characteristics of the Independent Curriculum. Apart from that, students are also able to practice the learning process in accordance with the characteristics of the Independent Curriculum. In this way, students are equipped with competencies that suit the needs of the field to prepare educators who can be competitive in the world of education.